The economic impact of a ban on imports of air freithed organic products to the UK - Peter Gibbon; Simon Bolwig (Danish Institute for International Studies (DIIS), 2007)
Against the background of growing concern about climate change, some European private organic standard-setting bodies led by the Soil Association are considering whether to refuse certification of organic produce imported by air. Their right to determine the rules to which they certify produce, irrespective of whether this is already certified to EU public rules, has been recently re-affirmed in the process of the revision of EU Organic Regulation. A change in Soil Association rules along these lines may have a significant impact, firstly because UK super-markets have historically favoured that their suppliers certify to Soil Association rules, and secondly because air freighting of organic produce to the UK has increased considerably in recent years. This increase is related to UK supermarkets' embrace of organic sales, in a context where competition between supermarkets over fresh produce market share emphasises widening the product range and securing its year-round availability.
Keywords: 330; Importbeschränkung; Biokost; Luftfrachtverkehr; Wirkungsanalyse; Großbritannien